Stitch bond strength study in insulated Cu wire bonding - Leong, H.Y.; Yap, B.K.; Khan, N.; Ibrahim, M.R.; Tan, L.C.; Faiz, M. (Maney Publishing, 2014)
The market demands for higher pin counts and more chips functionality pose challenges in conventional wire bonding. However, insulated Cu wire technology enables fine and ultra-fine pitch wire bonding as the insulator coating on the bare wire prevents wires shorting problem. This paper presents the study on the stitch-bonding process optimisation and its challenges for the insulated Cu wire with a diameter of 20 mu m. Insulated Cu stitch bond samples show 37% lower stitch pull strength than that of bare Cu. The cross-sectioned insulated Cu stitch bond shows that there is an insulation residue between the Cu stitch and the Au-plated substrate, potentially resulting in lower stitch pull performance. However, after isothermal aging at 225 degrees C for up to 78 hours, the stitch pull results for insulated Cu wire passed the industry reliability standard, without any lifted bond. A detailed comparison study was performed for the insulated Cu and the bare Cu stitch bonding.